Involvement of CREB-regulated transcription coactivators (CRTC) in transcriptional activation of steroidogenic acute regulatory protein (Star) by ACTH. (1st January 2020) - Smith, Lorna I.F.; Huang, Victoria; Olah, Mark; Trinh, Loc; Liu, Ying; Hazell, Georgina; Conway-Campbell, Becky; Zhao, Zidong; Martinez, Antoine; Lefrançois-Martinez, Anne-Marie; Lightman, Stafford; Spiga, Francesca; et al.
Abstract: Studies in vivo have suggested the involvement of CREB-regulated transcription coactivator (CRTC)2 on ACTH-induced transcription of the key steroidogenic protein, Steroidogenic Acute Regulatory (StAR). The present study uses two ACTH-responsive adrenocortical cell lines, to examine the role of CRTC on Star transcription. Here we show that ACTH-induced Star primary transcript, or heteronuclear RNA (hnRNA), parallels rapid increases in nuclear levels of the 3 isoforms of CRTC; CRTC1, CRTC2 and CRTC3. Furthermore, ACTH promotes recruitment of CRTC2 and CRTC3 by the Star promoter and siRNA knockdown of either CRTC3 or CRTC2 attenuates the increases in ACTH-induced Star hnRNA. Using pharmacological inhibitors of PKA, MAP kinase and calcineurin, we show that the effects of ACTH on Star transcription and CRTC nuclear translocation depend predominantly on the PKA pathway. The data provides evidence that CRTC2 and CRTC3, contribute to activation of Star transcription by ACTH, and that PKA/CRTC-dependent pathways are part of the multifactorial mechanisms regulating Star transcription. Highlights: ACTH induces CRTC1-3 translocation to the nucleus in Y1-BS1 and ATC7-L cells. This parallels increases in pCREB and precedes initiation of Star transcription. CRTC2 and CRTC3 bind the Star promoter during transcriptional activation. Inhibition or knockdown of CRTC1-3 attenuates ACTH-induced Star transcription. Implicates role for CRTC 2 and 3 in multifactorial regulation of Star transcription.